1284. Study of Single Nucleotide Polymorphisms Associated with HIV-1 Set-Point Viral Load in Antiretroviral Therapy-Naïve HIV-Positive Participants of the START Study. (26th November 2018) - Ekenberg, Christina; Tang, Man-Hung Eric; Murray, Daniel D; MacPherson, Cameron; Sherman, Brad T; Losso, Marcelo; Wood, Robin; Paredes, Roger; Molina, Jean-Michel; Helleberg, Marie; Jina, Nureen; Kityo, Cissy M; et al.
Abstract: Background: HIV-1 set-point viral load (SPVL) is predictive of disease progression and shows variability across HIV-1-positive (HIV+) persons. Various factors may influence SPVL including viral features, environmental exposure and host genetics. To identify single nucleotide polymorphisms (SNPs) associated with SPVL, we performed a genome-wide association study (GWAS) on a subset of participants from the Strategic Timing of AntiRetroviral Treatment (START) study covering a demographically diverse population. Methods. Consenting participants were antiretroviral therapy (ART)-naïve and SPVL was taken as log10 (HIV RNA) at study entry. Genotypic data were generated on a custom content Affymetrix Axiom SNP array covering 770, 558 probes. The Ensembl Gene database, assembly GRCh37.p13, was used for annotation. Principal component analysis (PCA) was used to identify population structures, and analysis of variance (ANOVA) was performed to detect associations between SNPs and SPVL. SNPs with zero variance or minor allele frequency (MAF) ≤0.05 were removed. Results. Among the 2, 544 participants, PCA showed distinct population structures with strong separation between black ( n = 578) and nonblack ( n = 1, 966) participants, Figure 1. ANOVA was performed independently on both subsets. Two SNPs located in the Major Histocompatibility Complex (MHC) class I region of chromosome six reached genome-wide significance ( P < 5 × 10 –8 ) in the non-black population: rs4418214 ( P = 1.74 × 10 -10 ), and rs57989216 ( P = 3.96 × 10 –8 ), Figure 2. Two additional SNPs, rs9264942 ( P = 5.99 × 10 –8 ) and rs7356880 ( P = 9.69 × 10 –8 ), in the same region approached significance. The minor alleles of all four SNPs were associated with lower SPVL, Figure 3. While no SNPs reached genome-wide significance in the black group, we observed similar trends toward lower SPVL for both rs4418214 and rs57989216. Conclusion. In this study we confirm the association of a previously reported SNP (rs4418214) and identify a novel candidate SNP (rs57989216) associated with lower SPVL in a population of nonblack, ART-naïve HIV+ persons. Current findings suggest that the effects of these SNPs are consistent across race groups, but further studies are required to confirm this. Our results support previous findings that variation in the MHC class I region is a major host determinant of HIV-1 control. Disclosures: D. D. Murray, Centre of Excellence for Health, Immunity and Infectious diseases (CHIP), Department of Infectious Diseases, Rigshospitalet, University of Copenhagen, Copenhagen, Denmark: Employee, Salary. J. M. Molina, Gilead: Scientific Advisor, Consulting fee. Merck: Scientific Advisor, Consulting fee. ViiV: Scientific Advisor, Consulting fee. Teva: Scientific Advisor, Consulting fee.